Regional simulation of coupled hydromechanical processes in fractured and granular porous aquifer using effective stress-dependent parameters - Preisig, Giona (My University, 2013)
Field observations and laboratory experiments have clearly demonstrated that heavily perturbed / exploited aquifers are subject to 3D deformations, which may cause significant socio-economic impacts at regional scale. Most common examples include: (1) excessive pumping of groundwater from deep aquifers leading to land subsidence; (2) deep excavation of tunnels in permeable geological units resulting in dangerous differential consolidation, especially for dams; and (3) fluid injection into deep reservoirs causing ground uplift and microsismicity. These manifestations are due to a substantial modification of water pressures within the aquifer, leading to effective stress variations, and deformations. Moreover, such deformations modify hydrodynamic parameters, i.e., hydraulic conductivity, porosity and storage coefficient. In confined or deep aquifer systems, hydrodynamic parameters have to be considered as effective stress-dependent variables. In such environments the assumption of constant parameters can lead to significant quantitative errors. The afore-mentioned fluid-to-solid hydromechanical processes seem to be essentially governed by hydrogeological, geomechanical and structural properties of the aquifer system. In order to take into account the major processes, as well as their principal properties, regional coupled hydromechanical simulation necessarily requires simplification of the governing equations to be operational in real, large scale, hydrogeological systems.
In the present thesis, model functions relating effective stress to hydrodynamic parameters are developed from fundamental hydrogeological and physical concepts, and implemented in the groundwater flow equation. Proposed stress-dependent equations are verified by a comparison with laboratory and field data. This is carried out for (1) fractured aquifers, i.e., consolidated rocks whose porosity results principally from the presence of fractures, cracks, joints and faults, and (2) granular porous aquifers, i.e., unconsolidated rocks whose porosity results from voids between solid grains. The relation between porosity and stress is also used to elaborate a deformation model for solving aquifer vertical volume change, i.e., ground settlement / uplift. A modelling approach is proposed in order to solve fluid-to-solid hydromechanical processes at regional scale, considering detailed geological structures. In this numerical method, hydrodynamic parameters are considered as stress-dependent variables.
Exact analytical solutions solving flow in a media under stress are developed in order to verify the numerical method. The proposed approach is then applied to the analysis of real case studies. In particular, to (1) the abnormal deformation of the Zeuzier arch dam (Wallis, Switzerland) due to the drainage of an unexpected confined aquifer by the Rawyl exploratory adit; (2) the problematic of water inflow into tunnels based on the geological investigations undertaken by the Lyon-Turin railway project for the 57 km basis tunnel; as well as (3) the anthropogenic land subsidence affecting the Mexico City basin.
Quantitative studies of deep aquifer systems considering constant hydrodynamic parameters result in non-accurate volumetric discharge rates and pressure head fields. On one hand, increasing effective stress leads to decreasing hydrodynamic parameters. This results in a diminution of volumetric flow rates through a deep reservoir or in a deep excavation. Moreover, the decrease of water pressure is slowed down due to the decrease of hydraulic conductivity. This has repercussion on consolidation time. On the other hand, if - and only if - the rock is elastic, decreasing effective stress can lead to increasing hydrodynamic parameters and volumetric discharge rates.
For analytical solutions of volumetric discharge rate in deep wells or into a tunnel, the dependency of hydrodynamic parameters on effective stress can be taken into account by using a factor allowing stress consideration; whereas, in numerical analysis, such a process can be considered by implementing stress-dependent parameters in the groundwater flow and aquifer deformation models.
The proposed numerical approach for fluid-to-solid coupled hydromechanical processes, is computationally simple, based on few unknowns, and efficiently reproduces regional consolidations in geologically oriented 3D meshes. This method is critical for hydrogeological and geomechanical quantitative studies investigating the sensitivity of deep aquifers on decreasing / increasing effective stresses. In particular for regional scale projects where water pressure may be subject to substantial modifications, such as dam construction or tunnel excavation, geologic radioactive waste repositories, deep reservoir exploitation for CO2 sequestration, geothermal energy production, as well as extraction of groundwater and / or hydrocarbons.
Thèse de doctorat : Université de Neuchâtel, 2013
Keywords: hydromechanical coupling; fractured aquifers; granular porous aquifers; hydraulic conductivity; storage coefficient; porosity; effective stress; modelling; regional scale